The Role of the γδ T Cell in Allergic Diseases - Rui Zheng; Qintai Yang (Journal of Immunology Research)
The predominant distribution of γδ T cells in the mucosal and epithelial tissues makes these unconventional lymphocytes the “guards” to contact external environment (like allergens) and to contribute to immune surveillance, as well as “vanguards” to participate in initiating mucosal inflammation. Therefore, γδ T cells have been considered to bridge the innate and adaptive immunity. The role these cells play in allergy seems to be complicated and meaningful, so it makes sense to review the characteristics and role of γδ T cells in allergic diseases.